Blue-green small-signal gain and saturation in a luminescent polymer gain medium - BLAU, WERNER (My University, 2006)
The authors study the optical gain and saturation behavior in a blue-green-emitting luminescent polymer gain medium. Based on the results of amplified spontaneous emission measurements, the gain coefficients, the gain-length product, and the corresponding small-signal gain are determined. By the use of the variable stripe length method, large net gain coefficients of up to 106?6 cm ?1 have been measured under nanosecond photopumping. The large gain has favorable implications for the development of short wavelength lasers and amplifiers. Their study shows that a small-signal gain of 19 dB is achievable with a very compact optical amplifier with a 400 m length.
PUBLISHED
Keywords: blue-green-emitting luminescent polymer gain medium; blue-green-emitting luminescent polymer gain medium